Pulsed field ablation for ventricular arrhythmias with pentaspline catheter - Padisak, Anna; Szegedi, Nándor; Tanai, Edit; Salló, Zoltán; Nagy, Klaudia Vivien; Perge, Péter; Boga, Márton; Orbán, Gábor; Tóth, Patrik; Komlósi, Ferenc; Merkely, Béla; Gellér, László (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCatheter ablation using pulsed-field energy may penetrate deeper into scarred tissue than thermal energies; however, evidence regarding its role in treating ventricular arrhythmias (VAs) is limited. In this prospective study, we report our current experience on pulsed field ablation (PFA) with pentaspline catheter for the treatment of premature ventricular contractions (PVCs) originating from the right ventricular outflow tract (RVOT) and scar-related ventricular tachycardias (VTs).MethodsConsecutive VA patients who underwent PFA with Farapulse system were enrolled. Seven patients underwent ablation for idiopathic RVOT PVCs, and five patients with structural heart disease underwent ablation for scar-related VTs. The recurrence of arrhythmias was assessed by 24-hour Holter electrocardiography monitoring or implantable cardioverter defibrillator interrogation.ResultsTwelve patients were enrolled, age 51 ± 9 years, nine were men, four had previously failed radiofrequency ablation. Procedural and fluoroscopy times were 53 (41–105) minutes and 8 (4–20) minutes, respectively. The median number of PFA applications was 20 ± 13 in the VT group and 8 (7–8) in the PVC group. Acute procedural success was achieved in 92% (CI 62%–100%) of patients. During a mean follow-up of 100 (97–140) days, freedom from VT was 80% (CI 28%–99%), and a PVC burden <1% was achieved in 71% (CI 29%–96%) of patients.ConclusionThe ablation of idiopathic RVOT PVCs and scar-related VTs with the pentaspline PFA catheter is feasible, with good acute and mid-term efficacy observed in our cohort. Further research involving larger cohorts and longer follow-up periods is needed to analyze the safety and define the role of PFA in VAs.